2020
DOI: 10.1093/cercor/bhaa107
|View full text |Cite
|
Sign up to set email alerts
|

Foxg1 Upregulation Enhances Neocortical Activity

Abstract: Foxg1 is an ancient transcription factor gene orchestrating a number of neurodevelopmental processes taking place in the rostral brain. In this study, we investigated its impact on neocortical activity. We found that mice overexpressing Foxg1 in neocortical pyramidal cells displayed an electroencephalography (EEG) with increased spike frequency and were more prone to kainic acid (KA)-induced seizures. Consistently, primary cultures of neocortical neurons gain-of-function for Foxg1 were hyperactive and hypersyn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
3

Relationship

4
4

Authors

Journals

citations
Cited by 12 publications
(28 citation statements)
references
References 82 publications
0
21
0
Order By: Relevance
“…Mecp2 overexpression in these models led to electrographic discharges accompanied by behavioral seizures in mice [ 209 , 211 ]. Foxg1 overexpression in mice deep-layer neocortical projection neurons also led to higher neuronal excitability assessed by frequency of electrographic high-amplitude spikes and severity of behavioral seizures induced by kainic acid [ 212 ].…”
Section: Resultsmentioning
confidence: 99%
“…Mecp2 overexpression in these models led to electrographic discharges accompanied by behavioral seizures in mice [ 209 , 211 ]. Foxg1 overexpression in mice deep-layer neocortical projection neurons also led to higher neuronal excitability assessed by frequency of electrographic high-amplitude spikes and severity of behavioral seizures induced by kainic acid [ 212 ].…”
Section: Resultsmentioning
confidence: 99%
“…The lentiviruses were generated and titrated as previously described [ 62 ]. Lentiviral vectors employed in this study include: LV_pGfap-rtTA2S-M2, (built as previously shown [ 63 ]) and LV_TREt-mCherry, kindly provided by professor Antonello Mallamaci's lab. The slices were infected with 5 µL of lentiviral preparation, whose titres were 4 × 106 and 1 × 107 respectively.…”
Section: Methodsmentioning
confidence: 99%
“…Shut down to allow neuronogenic precursors exit from cell cycle, Foxg1 is normally reactivated in newborn murine neurons [8], where it is needed to finely tune layer identity [9,10], dendritic architecture [5,11,12] as well as activity and excitability [14]. All that offers further valuable opportunities to functionally score mutant FOXG1 alleles against their wild type counterparts.…”
Section: Functional Characterization Of Foxg1 G224s Foxg1 W308x and ...mentioning
confidence: 99%
“…It biases neocortical neurons to specific layer identities [7][8][9][10] and promotes their morphological maturation [5,[11][12][13]. Moreover, it sustains activity and excitability of these neurons [13,14], being in turn upregulated by neuronal activity [14,15]. As a consequence of that, experimental Foxg1 manipulation in mouse models results in prominent, cognitive and behavioral, phenotypes.…”
Section: Introductionmentioning
confidence: 99%